Menghidupkan Kembali Gagasan Ekonomi Koperasi sebagai Fondasi Perekonomian Nasional - Hamdan Hamdani (UIN Siber Syekh Nurjati Cirebon, 2020)
This research is motivated by the author's interest in studying the economic ideas of cooperatives contained in Article 18 of the 1945 Constitution. Cooperatives as a joint venture is able to reflect the provisions as in family life. In a family, everything that is done together is aimed at the common interests of all family members. Cooperatives are established and built to create an economic system that guarantees more equitable distribution so that economic control is not concentrated in a group of people. So that everyone can achieve prosperity through joint efforts. The purpose of this study is to find out how the economic ideas of cooperatives can be used as a foundation of the national economy. The research method used in this research is the literature study research method. The conclusion of this research states that cooperatives have the characteristics of economic democracy, which is economic activities are regulated by the people, carried out by the people, and aimed at people's welfare. Therefore, if the cooperatives economic system is implemented in a consistent and sustainable, it is not impossible that the economic problems which still hold the Indonesian people will gradually be overcome